DAMPAK PERCERAIAN ORANGTUA AKIBAT KDRT TERHADAP KECEMASAN ANAK PEREMPUAN DEWASA AWAL - Kiki Cantika; Untung Subroto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Families, as the smallest social unit, often face serious problems such as domestic violence that can result in divorce and have a deep psychological impact on children, including anxiety. Data shows that in 2023, there will be 5,174 divorce cases in Indonesia due to domestic violence. This study aims to determine the description of anxiety in early adult women who are victims of parental divorce due to domestic violence. This research was conducted using a qualitative approach, with interview and observation data collection methods. This research was conducted on six participants. The results showed that 6 subjects experienced anxiety caused by the divorce of parents who experienced domestic violence. The impact of anxiety on the 6 subjects is a psychological impact but of the 6 there are 2 subjects who experience physical impacts. The 6 subjects can also be said to experience realistic, neurotic, and moral anxiety.